Relation between acute pancreatitis and diabetic emergencies: a literature review (Research, Society and Development, 2022)
Acute pancreatitis (AP) is an inflammatory disease that affects the pancreas and peripancreatic tissues, while diabetic keatoacidosis (DKA) is a metabolic disorder resulting from a hyperglycemic state, with a state of metabolic acidosis and ketosis. About 77% of patients with DKA have signs of pancreatic disease. The objective of this study is to analyze the correlation of AP with diabetic emergencies and encourage medical professionals to explore this topic in view of the growing number of AP cases associated with DKA. This is an integrative literature review carried out through electronic searches in the following databases: PubMed, Scielo and Lilacs in March 2022. In these searches, the following descriptors were applied together with the Boolean operator AND: Pancreatitis AND Hyperosmolar Hyperglycemic State AND Diabetic Ketoacidosis, Pancreatitis AND Hyperosmolar Hyperglycemic State and Pancreatitis AND Diabetic Ketoacidosis. The guiding question to guide the correct search for articles was “What is the relation between acute pancreatitis and diabetic emergencies?” The research was carried out from a review of published studies on the correlation of DKA or hyperosmolar hyperglycemic state (HHS) with AP, and the association between cause and effect. In addition, most articles showed the development of hypertriglyceridemia (HTG) as a consequence of this hyperglycemic state. The reports follow two pathophysiological biases, the first correlating ketoacidosis as the cause of acute pancreatitis, and the second based on acute pancreatitis as the cause of diabetic ketoacidosis. It is concluded that the relationship between AP and diabetic emergencies appears in different ways. There are cases in which pancreatic inflammation is responsible for complications and cases in which it is a consequence of these. Hypertriglyceridemia is also present and can often be the cause of acute pancreatitis in conjunction with ketoacidosis.